A nationwide survey on the expectation of public healthcare providers on family medicine specialists in Malaysia—a qualitative analysis of 623 written comments. Issue 6 (11th June 2014) - Chew, Boon-How; Cheong, Ai-Theng; Ismail, Mastura; Hamzah, Zuhra; A-Rashid, Mohd-Radzniwan; Md-Yasin, Mazapuspavina; Ali, Norsiah
Abstract : Objective: To examine the expectation of public healthcare providers/professionals (PHCPs) who are working closely with family medicine specialists (FMSs) at public health clinics. Design: Cross-sectional study. Setting: This study is part of a larger national study on the perception of the Malaysian public healthcare professionals on FMSs. Participants: PHCPs from three categories of health facilities, namely hospitals, health clinics and health offices. Main outcome measures: Qualitative analysis of written comments of respondents' expectation of FMSs. Results: The participants' response rate was 58% (780/1345) with an almost equal proportion from each public healthcare facility. We identified 21 subthemes for the 623 expectation comments. The six emerging themes are (1) need for more FMSs, (2) clinical roles and functions of FMSs, (3) administrative roles of FMSs, (4) contribution to community and public health, (5) attributes improvement and (6) research and audits. FMSs were expected to give attention to clinical duty. Delivering this responsibility with competence included having the latest medical knowledge in their own and others' medical disciplines, practising evidence-based medicine in prehospital and posthospital care, better supervision of staff and doctors under their care, fostering effective teamwork, communicating more often with hospital specialists and making appropriate referral. Expectations ranged from definite and strong for more FMSs at the health clinics to low expectation for FMSs' involvement in research; to mal-expectation on FMSs' involvement in community and public health programmes. Conclusions: There were some remarkable differences in expectations on FMSs from the three different PHCPs. These ranged from being clinically competent and administratively available for patients and staff at the health clinics, to mal-expectations on FMSs to engage in public health affairs. Relevant parties, including FMSs themselves, could take appropriate self-improvement initiatives to enhance public practice of family medicine and patient care. Trial registration number: NMRR ID: 08-12-1167.